EKSISTENSI PENDIDIKAN ANTI KORUPSI: NILAI, PERAN, DAN TANTANGANNYA DALAM MEMBANGUN GENERASI BERINTEGRITAS - Mayang Pasa; Riffasyha Nilam Hernisa; Shintya Rahmanda Putri (Kampus Akademik Publiser, 2026)
This study discusses the existence of anti-corruption education, which contains values, roles, and challenges in building a generation with integrity. Using a normative juridical and ethnographic approach through interviews, literature studies, and field documentation, it was found that anti-corruption education plays an important role in instilling the values of honesty, responsibility, and legal awareness as the foundation for forming an integrity-based character. Although it still faces challenges such as low moral awareness, environmental influences, and the suboptimal implementation within the education system, this education remains relevant and strategic as a preventive effort to create a generation with integrity in the modern era.